Development And Quality Evaluation Of Malaysian Jackfruit 'Dadih' Using Cow's Milk And Goat's Milk - Chye, Su Jin (2013)
Dadih incorporated with jackfruit purees (Artocapus heterophyllus Lam.) was made by using cow’s milk and goat’s milk. Four types of different dadih was prepared, namely control cow’s milk dadih (CD), jackfruit incorporated cow’s milk dadih (JCD), control goat’s milk dadih (GD), and jackfruit incorporated goat’s milk dadih (JGD). In the initial study, textural properties of dadih were investigated for the optimum formulation of jackfruit incorporated dadih by using response surface methodology (RSM) approach. The experimental study was carried out by using 3-level full factorial design which revealed that the percentage of carrageenan and percentage of jackfruit purees were the two significant independent variables.